Survival Of Bifidobacteria And Other Selected Intestinal Bacteria In Tpy Media Supplemented With Curcumin As Assessed In Vitro - Jazayeri, Seyed Davoud (2007)

(untitled)
Bacteria belonging to the genera Bifidobacterium and Lactobacillus are most often used as probiotic. They exert beneficial properties with regard to human health, such as inhibition of growth of exogenous and/or harmful bacteria, stimulation of immune functions, anti-tumour properties, cholesterol reduction, aid in digestion and/or absorption of food ingredients/minerals and synthesis of vitamins. Foods are thought to be among the major factors that can affect the gut microbial balance. The gut is the site of active bioconversions and absorption of foodstuffs that have not been absorbed in the upper gastrointestinal tract. These include components especially plant-derived such as phenolic and other aromatics components. One of the most common sources of phenolic and aromatics in diets is curcumin derived from turmeric (Curcuma longa L.).The growth of two Bifidobacterium strains (Bifidobacterium longum BB536, Bifidobacterium pseudocatenulatum G4) and other selected intestinal bacteria (Lactobacillus acidophilus, Lactobacillus casei shirota, Enterococcus faecalis JCM 5803 and Escherichia coli K-12) were studied in 10 ml basal TPY medium containing various concentrations of curcumin (0.0025g, 0.005g, 0.0075g and 0.01g/10ml). Viable cell counts of the bacteria and their pH medium were determined during incubation period of 12h, 24h, 36h and 48h at 37oC anaerobically. The presence of curcumin did not change the pH of the medium as compared to the basal TPY without curcumin. In the absence of curcumin, growth of all the bacteria tested occurred within 12h expect that of B. pseudocatenulatum G4 within 24h, after which cultures entered into early stationary phase and finally into death phase. Therefore depending on the bacteria, no growth occurred after 12h or 24h incubation. Maximum carrying capacity attained by all organisms before entering into stationary phase was about 10 log CFU/ml. However, in the presence of curcumin, cultures showed various degrees of growth inhibition in comparison with basal TPY. E. faecalis and B. longum BB536 survived better than the other bacteria tested. The growth reduction percentage of E. faecalis grown in TPY medium supplemented with 0.0025g, 0.005g, 0.0075g and 0.01g of curcumin and incubated for 12h was 1%, 7%, 24% and 36%, respectively. At incubation period of 24h, the percentage of growth reduction was almost the same as for 12h of incubation. Interestingly, the percentage of growth reduction was greatly reduced to only 1%, 2%, 14% and 25% when incubated for 36h and 1%, 2%, 7%, and 8% when incubated for 48 h.B. longum BB536 was ranked second in term of their survivability in basal TPY medium supplemented with curcumin. After 12h of incubation, 0.0025g of curcumin inhibits 10% B. longum BB536 growth. At concentrations of 0.005, 0.0075 and 0.01g, B. longum growth was inhibited at 16, 44 and 48%, respectively. At incubation period of 24h, the percentage of reductions was not much different from 12 h for 0.075, and 0.01g of curcumin supplemented in the media, but slightly increased for the concentrations of 0.0025, and 0.005g curcumin. Interestingly, the incubation of the B. longum culture for 36 and 48h showed lower growth inhibition as compared to the 12 and 24h. The other intestinal bacteria tested showed higher growth inhibition percentage as compared with E. faecalis and B. longum. Among the bacteria tested, L. acidophilus recorded the most sensitive to curcumin. The inhibition rates showed more than 80% values for 0.005, 0.0075, and 0.01g of curcumin applied. Moreover, the surviving cells of L. acidophilus in the culture medium supplemented with the lowest concentration of curcumin (0.0025 g) decreased to almost the same values of the higher concentrations. Supplementation of the test medium with tween 80 increased the survivability of the bacteria tested. E. coli K-12 survived better than the other bacteria tested. The growth reduction percentage of E. coli K-12 grown in basal media supplemented with 0.01 ml of tween 80 and 0.0025 g of curcumin and incubated for 6h was 5% and 50%, respectively. At incubation period of 12h, the percentage of growth reduction in basal media supplemented with curcumin increased up to 60%, and with continuing incubation until 24h the percentage of growth reduction was reduced to 23%. At incubation period until 24h the percentage of growth reduction of E. coli K-12 in basal media supplemented with tween 80 was almost the same as for 6h of incubation (5%). The ability of the bacteria to degrade curcumin was studied using spectrophotometric method. On ultraviolet visible spectrophotometric study (UV-Vis spectra), the maximum light absorption bands obtained in TPY media supplemented with different concentration of curcumin was observed at 400.4 nm. Maximum absorption bands of curcumin in TPY media after 48 h incubation with the bacteria tested without any change was at 400.4 nm. Comparing the wavelength of curcumin before and after incubation with the bacteria proved that all the bacterial tested at this experiment are unable to degrade curcumin and it remained intact in media. To confirm the above finding, the amount of curcumin after 48 h of incubation with the bacteria was also calculated by standard curve. The absorbance of curcumin in wavelength of 400.4 nm in comparison with 0 h was reduced. Consequently, the amount of curcumin after incubation with all the bacteria tested decreased. The percentage reduction of 0.0025 and 0.0050 g of curcumin/10 ml was 56-60 and 18-24 % and for two other concentrations which were 0.0075 and 0.01g/10ml was 15-16 and 12-14 %, respectively. Curcumin, as a common aromatic, stimulant and coloring property in diet was found to possess antibacterial activity toward B. longum BB536, B. pseudocatenulatum G4 and other selected intestinal bacteria (L. acidophilus, L. casei shirota, E. faecalis JCM 5803 and E. coli K-12). The number of the surviving cells of all tested micro- organisms decreased drastically after 48 hours of incubation in comparison with the control in the basal TPY media.